2010
DOI: 10.1523/jneurosci.0054-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Central But Not the Basolateral Nucleus of the Amygdala Disrupts Learning in Response to Overexpectation of Reward: Figure 1.

Abstract: The amygdala is critical for associating predictive cues with primary rewarding and aversive outcomes. This is particularly evident in tasks in which information about expected outcomes is required for normal responding. Here we used a pavlovian overexpectation task to test whether outcome signaling by amygdala might also be necessary for changing those representations in the face of unexpected outcomes. Rats were trained to associate several different cues with a food reward. After learning, two of the cues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 63 publications
6
37
2
Order By: Relevance
“…Thus, the over-expectation paradigm provides a behavioral setting in which ABL and CeN may function in parallel rather than in serial. One possibility is that the role of CeN in overexpectation reflects the involvement of this area in supporting attentional function (Holland and Gallagher, 1993;Maddux et al, 2007;Calu et al, 2010) rather than any selective role in representing certain types of associative information. Additional studies are required to evaluate these possible explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the over-expectation paradigm provides a behavioral setting in which ABL and CeN may function in parallel rather than in serial. One possibility is that the role of CeN in overexpectation reflects the involvement of this area in supporting attentional function (Holland and Gallagher, 1993;Maddux et al, 2007;Calu et al, 2010) rather than any selective role in representing certain types of associative information. Additional studies are required to evaluate these possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the basolateral amygdala (BLA) and the orbitofrontal cortex (OFC) are two key components of the circuit important for such behavioral control (Jones and Mishkin, 1972). More recently, numerous studies have shown that both areas are necessary for changes in behavioral paradigms that reflect a knowledge of impending outcomes, such as reinforcer devaluation (Hatfield et al, 1996;Málkováet al, 1997;Gallagher et al, 1999;Baxter et al, 2000;Balleine et al, 2003;Izquierdo et al, 2004;Machado and Bachevalier, 2007;Ostlund and Balleine, 2008;Rudebeck et al, 2013b;Zeeb and Winstanley, 2013) and associative encoding in the two areas is typically interdependent Hampton et al, 2007;Rudebeck et al, 2013a). Although there is still some debate about the relative involvement of the two regions in learning versus using information (Blundell et al, 2001;Pickens et al, 2003Pickens et al, , 2005Wellman et al, 2005;Johnson et al, 2009;West et al, 2011;Zhang et al, 2013;Gore et al, 2015), these studies illustrate the close relationship between BLA and OFC in acquiring and then using outcome expectancies to guide behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This region projects to both the VTA and SNc (Gonzales and Chesselet 1990;Fudge and Haber 2000), which innervate the NAc and dorsal striatum, respectively, and these projections can have an indirect excitatory effect on a subpopulation of dopamine neurons through inhibition of local GABAergic interneurons (Rouillard and Freeman 1995;Chuhma et al 2011). The CeN is required to learn from (negative) reward-prediction error (Holland and Gallagher 1993;Holland et al 2001;Haney et al 2010) and CeN-SNc-projecting neurons will become activated after learning by reward-prediction error, suggesting that communication between these structures relates to reward-prediction errormediated learning (Lee et al 2010). An intact CeN is also required for the acquisition of conditioned-orienting (Gallagher et al 1990) and sign-tracking responding (Parkinson et al 2000), but is not required for more specific consummatory CRs (Chang et al 2012).…”
Section: Circuitry For General Motivational Valuementioning
confidence: 99%
“…Current data suggest that intra-central, but not basolateral, amygdala AMPA receptor stimulation may be involved in arousal and affective cue learning. Haney et al (2010) and Stalnaker and Berridge (2003) Some studies have found regionally-selective activations within the amygdala. For instance, c-Fos labelling suggested that medial CeA may be more involved in appetitive processing (for food-deprived rats in response to a cue signalling food, or water-deprived mice in a place preference task) while the BLA and lateral CeA may reflect salience processing.…”
Section: Amemori Andmentioning
confidence: 99%